A evasão no curso de Administração da Fagen: dimensões políticas, institucionais e contextuais - Bonnas, Juliana Santesso (2019)
Dropout in higher education is not a new phenomenon, although beeing current, it is common to public and private institutions in Brazil and abroad. Several studies have already been carried out in order to understand and mitigate the problem. Initial theories were that dropout was directly related to the student and his level of integration in his freshman’s year. With new studies, other perspectives, scenario’s changes and deepening of both the profile of the courses and students, other factors where included, such as the economic situation, parental background and level of education, technology’s influence, perspectives that each course offers, institutional environment, quality of the training and the teacher’s role. This study is focused on the Bussiness course and its dropout rates, offered by Faculty of Management and Business of the Federal University of Uberlândia, analyzing the political, institutional and contextual dimensions that are informative in the dropout process. It was analyzed the academic trajectory of 1,716 students, who joined the College in 2007-2017, with observations regarding gender, age, shift, form and period of withdrawal, admission process, academic performance and previous background. Also, 157 minute mettings of the Course’s Collegiate were analyzed, and 72 processes of student’s termination, 31 of which were set up between 2007 and 2013/1 and the remaining between 2013/2 and 2017. In order to confirm and complement the analyzes and observations, 08 interviews were carried out with staff members. The conclusions indicate that the course’s dropout rates were influenced by the Reuni, SiSU, affirmative policies, by the economic scenario and the student’s previous education background. It was also observed that the job market to a certain extent favors the withdrawal of Bussines undergraduates, either by the wide range of performance or because there are employment opportunities in which the academic degree is not a requiremet. It can be concluded that, although it is not possible to act on all the factors that motivate students dropout, institutional intervention plays a decisive role, by clarifying student’s perspective about the potentialities and requirements of the course, as well as better guiding, welcoming and bonding with graduating students who showed greater disposition and tendency to complete the course when feeling supported.